PENGARUH VARIABEL MAKROEKONOMI DAN KONDISI PASAR MODAL INTERNASIONAL TERHADAP INDEKS HARGA SAHAM GABUNGAN - Yusuf Simabur; Joan Marta (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2014)
This study aims to analyze the effect of macroeconomic variables and international capital market conditions on the stock price index, namely: Effect of macroeconomic variables and the International Capital Markets Index against JCI in short-term. Short- term and long term research is descriptive and associative. The type of data in this study is secondary data from the years 2004-2013 in the form of time series data obtained from the IDX Statistics and Bank Indonesia publications. The analytical method used is the Error Correction Model.Hasil study are (1) BI Rate, Exchange Rate and STI have significant effect on the composite index in the short term, but money supply, DJIA and CAC40 have not significant effect on the composite index. (2)Money Supply, , Exchange Rate, DJIA and STI have significant effect on the composite index in the short term, but BI Rate, and CAC40 have not significant effect on the composite index.Keyword: Composite Stock Price Index, Macroeconomic Variables, International Capital Markets Index and Error Correction Model.